(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2026)
Computing represents one of the most significant modern technological media, playing a vital role in fostering creative thinking, problem-solving, and learner skill development. Language education is a field that demands constant renewal and innovation in the processes of knowledge delivery and acquisition through the most advanced contemporary methods, with the goal of achieving effective and sustainable learning. Many world languages have successfully attained their pedagogical objectives through the integration of modern technological tools, most notably English, which serves as a living model of such success. Owing to its global reach, adaptability, and linguistic flexibility, English has become deeply embedded in diverse linguistic communities, exerting a profound influence across all spheres of life and solidifying its status as a dominant global language (Crystal, 2012; Warschauer, 2013). By contrast, the Arabic language today faces a series of crises and challenges, particularly in its teaching and learning, and especially among non-native speakers (Alrabai, 2020). The acquisition of any language relies fundamentally on the mastery of its core skills; therefore, this study focuses on the productive skills, speaking and writing, as the primary communicative channels that manifest the learner’s ability to express meaning both orally and in written form (Bygate, 2018). Through a descriptive and analytical lens, this research explores how technological approaches can enhance these skills within the broader framework of digital integration, highlighting pedagogical implications for Arabic language instruction in the modern era.